Pengaruh Pembelajaran Pendidikan Kewarganegaraan terhadap Pembentukan Karakter Siswa di Era Globalisasi - Cindy Rahmadani; Syamzaimar (Jurnal Inovasi Pendidikan Madrasah Ibtidaiyah, 2026)
The era of globalization brings significant challenges in the form of shifting cultural values and moral decadence among the younger generation. This research is motivated by the critical need to strengthen students' national identity so that it is not eroded by negative external influences. The purpose of this study is to analyze the effectiveness of Civic Education (PKn) in forming characters of discipline, responsibility, and nationalism in high school students. The method used in this research is a quantitative approach with a correlational design. Data were collected through questionnaires distributed to 100 student respondents and analyzed using simple linear regression techniques. The results indicate that there is a positive and significant influence…